A sustainable management model for the Lombongo natural tourism destination based on the 4A approach - Misnawaty Wantogia; Abdul Haris Panai; Marini Susanti Hamidun; Sukirman Rahim; Sunarty Suly Eraku; Iswan Dunggio (Interaction, Community Engagement, and Social Environment, 2026)
Background: This study was conducted at Lombongo Nature Tourism Destination, Bone Bolango Regency, Gorontalo Province, Indonesia. This study developed a sustainable management strategy for Lombongo Nature Tourism Destination to overcome the fragmented tourism management and the poor integration among the 4A components (attraction, accessibility, amenities and ancillary services). This study aimed to examine how these components interact within a structured system to support destination performance. Methods: A mixed-method explanatory approach was applied, involving 47 stakeholders through questionnaires, interviews, and focus group discussions. Data were analyzed using descriptive statistics and Interpretive Structural Modeling (ISM) to identify hierarchical relationships among key sustainability elements. Findings: 9 key elements formed a hierarchical system. Sustainable policy , institutional capacity, community participation, and green infrastructure serve as the foundation. Linkage elements, such as technology, environmental education, and biodiversity conservation, act as adaptive connectors. Dependent elements of green funding and the circular economy emerge as system outcomes. This confirms that sustainability depends on integrated and structured governance rather than isolated components. Conclusion: To achieve long-term effectiveness, sustainable tourism management in Lombongo requires a hierarchical and system-based approach that prioritizes governance, integration, and ecological conservation. Novelty/Originality of this article: This study uses ISM to transform the 4A framework into an integrated, system-based management model, moving beyond descriptive analysis toward structural and governance-oriented tourism modeling. The proposed model provides a practical governance framework that can assist policymakers and destination managers in prioritizing sustainable tourism interventions through integrated institutional, environmental, and community-based strategies.